Whitehead at Harvard : 1924-1925 - Henning, Brian G.; Petek Joseph (Edinburgh scholarship online., 2020)
"In these newly commissioned essays, leading Whitehead scholars ask a range of important questions about Whitehead's first year of philosophy lectures. Do these lectures challenge or confirm previous understandings of Whitehead's published works? What is revealed about the development of Whitehead's thought in the crucial period after London but before the publication of Science and the Modern World? What should we make of concepts and terms that were introduced in these lectures but were never incorporated into subsequent publications? Also included in this volume is the text of Whitehead's first lecture at Harvard, recently gifted to the Critical Edition of Whitehead, allowing for a clearer understanding of Whitehead's plans and goals for his first course of lectures in philosophy than has previously been possible."--